Tantangan KPU di Era Digital: Antara Transparansi dan Keamanan Data di Kota Palangka Raya - Ramadhani Alfin Habibie; Ahmad Ahmad; Dody Wahyudi; Muhammad Aditya; Muhamad Hobiri; M. Syahbintang (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of information technology has produced a significant transformation in election administration mechanisms, including within the City of Palangka Raya. The digitalization of various services and information systems requires the General Elections Commission (KPU) to enhance transparency while simultaneously ensuring the security of voter data and election results. This study aims to examine the key challenges faced by the Palangka Raya KPU in balancing the need for information openness with data protection in the digital era. The research employs a qualitative descriptive method through literature review, direct observation, and structured interviews with KPU staff, election supervisors, and relevant stakeholders. The findings indicate that digitalization improves the effectiveness of public information dissemination, including through the use of Sidalih and Sirekap, yet it also introduces vulnerabilities such as potential voter data breaches, cyberattacks, and the spread of disinformation through social media. Moreover, limitations in human resources with technological expertise serve as constraints in optimizing digital security. Conversely, the implementation of data security standards and improvements in voter digital literacy contribute to strengthening public trust in the election process. Thus, the Palangka Raya KPU needs to reinforce cybersecurity infrastructure, enhance internal technical capacity, and broaden public education programs to safeguard electoral integrity amid increasing transparency demands and digital risks. Collaboration among government, academia, and the community is a strategic element in maintaining the quality of democracy in the digital era.